Nanoencapsulation of hydrophobic and low-soluble food bioactive compounds within different nanocarriers. (March 2019) - Rezaei, Atefe; Fathi, Milad; Jafari, Seid Mahdi
Abstract: There are many hydrophobic or poorly soluble nutrients and bioactive compounds which are essential for human health, such as phenolic compounds, carotenoids, essential oils, essential fatty acids, and insoluble vitamins. The low bioavailability and sustainability of these compounds are the main challenges for their use in the pharmaceuticae and food industries. Nanoencapsulation can be a favourable approach for protecting hydrophobic food bioactive compounds against unsuitable circumstances and enhance their bioavailability. In this review, several nanoencapsulation delivery systems for hydrophobic compounds, such as inclusion complexes through cyclodextrins, amylose, and yeast cells, nanogels, nanoemulsions, nanofibers, nanosponges, nanoliposomes, and nanoparticles made with lipids and biopolymers are discussed. Also, the toxicity and safety aspects of the nanocarriers loaded with hydrophobic food bioactive compounds has been covered. Different studies on encapsulation of hydrophobic food bioactives have shown that by incorporating them into sophisticated nanocarriers, promising and favourable results can be achieved such improvement in water solubility, antioxidant and other health-promoting properties, in vitro gastrointestinal release profile, and better protection against process and environment harsh conditions such as light, oxygen, high temperatures, humidity, etc. Graphical abstract: Image Highlights: There are many hydrophobic nutrients which are essential for human health. Hydrophilic nanocarriers can increase solubility and bioavailability of bioactives. Different nanocarriers for hydrophobic bioactive compounds can be applied. Toxicity and risks of nanocarriers loaded with bioactives should be considered.